1997
DOI: 10.1002/clc.4960200315
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte magnesium and prostaglandin dynamics in chronic sleep deprivation

Abstract: SummaryBuckground and hypothesis: The mechanism of sudden cardiac death occurring in patients with chronic fatigue is controversial. This study was designed to define a hypothesis that coronary arterial spasm and thrombus formation can occur during chronic fatigue.Meth0d.Y: For evaluating the feasibility of coronary arterial spasm, erythrocyte magnesium (Mg) was measured. Blood coagulability was evaluated by the change of prostaglandin concentration. Subjects included 16 healthy male volunteers (mean age 2 I .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
1
9
0
1
Order By: Relevance
“…19 In addition, both experimental and human studies revealed that mental and psychosocial stress decrease endothelial function. 11,20,21 According to Tanabe et al 's reports,4,6 the decreased levels of intracellular magnesium in this study were identical to those between temporary and persistent sleep deprivative conditions; they are thus considered to be a reflection of sleep deprivation in our study protocol.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…19 In addition, both experimental and human studies revealed that mental and psychosocial stress decrease endothelial function. 11,20,21 According to Tanabe et al 's reports,4,6 the decreased levels of intracellular magnesium in this study were identical to those between temporary and persistent sleep deprivative conditions; they are thus considered to be a reflection of sleep deprivation in our study protocol.…”
Section: Discussionsupporting
confidence: 78%
“…Sleep deprivation has been reported to decrease the intracellular magnesium level in humans, 4,6 and mental stress has also recently been reported to cause transient endothelial dysfunction in the brachial artery in humans; 11 however, the relationship between intracellular magnesium levels and endothelial function has not yet been fully investigated. Magnesium is considered to be a physiologic calcium antagonist and has been reported to decrease vascular tone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnesium content in four brain areas was also highly and positively correlated with the length of sleep periods (Chollet et al, 2000). Erythrocyte magnesium concentrations are low in adult human subjects with chronic sleep deprivation (1.1 ± 0.4 mg/dl) versus a control group (1.8 ± 0.4 mg/dl) (Tanabe et al, 1997). The reduction of sleep time is frequently associated with chronic fatigue.…”
Section: Relationship Between Magnesium and Neurosesmentioning
confidence: 95%